FINITE ELEMENT ANALYSIS OF EMBANKMENTS ON SOFT CLAYS - CASE STUDIES - Yousif J. al-shakarchi; Mohammed Yousif Fattah; Ahmed S. Jawad Al- Shammary (Journal of Engineering, 2009)
In order to design structures on soft soils, it is necessary to predict the behavior of the soft soil under imposed structure load. The high excessive settlements of the soft soil can cause many problems for the structures built on the soil like cracking and breakup of pavements, railway, highway embankments, etc... In this work, the finite element method is utilized as a tool for carrying out different analyses of embankments on soft ground with different conditions. The computer program CRISP (CRItical State Program) is developed to suit the problem requirements. CRISP uses the finite element technique and allows predictions to be made of soil deformations using the critical state theory. Eight-node isoparametric quadrilateral element has been added to the program. The program was used to analyze fully coupled (Biot) consolidation of two-dimensional plane strain problems. The finite element predictions of displacements and excess pore water pressures were compared with field measurements. It was concluded that the maximum vertical movement occurs below the centerline of the embankment. The settlement decreases slightly as the toe of the embankment is approached and decreases rapidly as the distance away from the toe increases. Upward movement of the surface far from the toe is observed. The maximum horizontal movement occurs near the top boundary. The rate of horizontal movement at the top of the foundation is greater than at the bottom. This behavior may be due to the flexibility and free movement condition of the vertical boundary in the top half